Tracing Value-Added and Double Counting in Gross Exports - Koopman, Robert; Wang, Zhi; Wei, Shang-Jin (American Economic Review, 2014)
This paper proposes a framework for gross exports accounting that breaks up a country's gross exports into various value-added components by source and additional double counted terms. By identifying which parts of the official trade data are double counted and the sources of the double counting, it bridges official trade (in gross value terms) and national accounts statistics (in value added terms). Our parsimonious framework integrates all previous measures of vertical specialization and value-added trade in the literature into a unified framework. To illustrate the potential of such a method, we present a number of applications including re-computing revealed comparative advantages and the magnifying impact of multi-stage production on trade costs.